Potret Kemampuan Literasi Membaca Siswa SDN Sambirejo 01 Kecamatan Bringin Kabupaten Semarang - Damayanti, Clara Lolyta Putri; Purnamasari, Iin; Kiswoyo, Kiswoyo (Universitas PGRI Semarang, 2025)
This study aims to gain an in-depth understanding of the reading literacy skills of Phase A students (Grade II) at SDN Sambirejo 01, Bringin District, Semarang Regency, through an ethnographic approach. It explores literacy practices both inside and outside the classroom, the social interactions involved in reading activities, students' perceptions of reading, as well as the social and cultural factors that influence the development of their reading literacy skills. The ethnographic method was applied using a series of in-depth and comprehensive qualitative data collection techniques. Semi-structured interviews were conducted with Grade II students to understand their perspectives, experiences, and beliefs related to reading. Interviews were also conducted with the school principal and Phase A classroom teachers to obtain their views on students' literacy development, reading instruction strategies, and the challenges faced in the process. The factors affecting students' reading abilities include internal factors (such as interest, individual abilities, and personal characteristics) and external factors (such as the learning environment, family support, the socio-cultural context of the school, and the socio-cultural context of the community). This study is expected to provide valuable insights for teachers, schools, and educational policymakers in designing and implementing more effective and contextual literacy instruction strategies, as well as in fostering students' interest in reading and improving their literacy skills from an early age. The researcher suggests developing and implementing reading literacy programs that have not yet been realized and promoting social and cultural character development through reading literacy activities.